أثر برنامج التعليمي وفق التقويم بحسب وقت إجرائه في تعلم المهارات في الجمناستك الفني لدى طالبات كلية التربية البدنية وعلوم الرياضية - السفاح, رغداء حسين; كشوش, غصون عبد الأمير ناصر (Sulaimani Journal for Humanities, 2018)
The impact of the educational program in accordance with the calendar according to the time of the vote in learning the skills in artistic gymnastics at the students in the Faculty of Physical Education and Sports Science Through observation, the researchers found a state of the link between the curriculum and the goals set and the interaction of the students in the educational process, where the presence of the ultimate goals case only Chebha mystery for special educated if not accompanied by targets for progress or youthful help the students to interact with exercises and lessons real sense of the progress level of skill As a result, they have a weakness in the development of learning skills. So the researchers felt the use of Afattrah goals as an essential part of the lesson dictated by FIG devices for students and gradient tasks and exercise applications according to the current level and use them compatible with the bjectives of their true potential The study was aimed at the following: 1- .knowledge of the educational program in accordance with the calendar according to the time of the vote in learning skills performance of some skills ( pivot Sarji a parallel Alaratvaat- various human wheel on the balance beam ) Technical 'body But presumably they search: 1. There are significant differences between the pre and post measurement differences for the benefit of telemetric in the evolution of some of the technical skills ' body . Researchers experimental method was used to design unequal groups in the search experience, and represented a sample of the research students of the third stage in the college of physical education and sports sciences / University of Babylon has been reached (22), a student of (11) students per group (experimental and control) The curriculum lasted 12 weeks and by educational unit once a week and was the unit time (90) minutes. After conducting tests on the tribal sample was tutorial using formative objectives of the application, and was later made a posteriori tests, in order to reach results data were analyzed statistically, while the results are presented and discussed to reach a group of The following conclusions were most important: 1. Through the findings of the researchers have been able to come to the following conclusions: 2. The objectives for the use of formative positive impact in the development of skill on the parallel pivot Sarji different heights in artistic gymnastics for students. 3 .The positive impact of the objectives of the training does not appear to learn the skill of the human wheel on the balance beam in the artistic gymnastics for students